القلق الاجتماعي وعلاقته بالمهارات الاجتماعية لدي المقيمين وغير المقيمين بالمدن الجامعية من طلاب جامعة الإسكندرية: دراسة سيكومترية إكلينيكية - محمود، هويدة حنفي (الجمعية المصرية للدراسات النفسية, 2012)
هدف البحث الحالي إلى دراسة القلق الاجتماعي لدى طلاب الجامعة، المقيمين من أسرهم، والمقيمين بالمدن الجامعية وعلاقته بالمهارات الاجتماعية لديهم، واشتملت العينة على (160) طالبا وطالبة، من المقيمين بالمدن الجامعية بكليات (التجارة – الخدمة الاجتماعية – الحقوق – الآداب – الهندسة – العلوم – الزراعة – الطب – الصيدلة)، و(390) طالبا وطالبة من المقيمين مع أسرهم من ذات التخصص ومن نفس الكليات، وتكونت العينة السيكومترية من (550) طالبا وطالبة، بواقع (270) طالبا، و(380) طالبة، وتكونت العينة الإكلينيكية من حالتين حصلا على أعلى الدرجات في المقياسين، وتم تطبيق أدوات البحث وهي مقياس القلق الاجتماعي للمراهقين والشباب من إعداد الباحثة، ومقياس المهارات الاجتماعية من إعداد محمد عبد الرحمن (1992).، والمقابلة الحرة، واستمارة دراسة الحالة من إعداد آمال باظة (1993) وقد أسفرت النتائج عن: • وجود نسبة انتشار دالة إحصائيا للقلق الاجتماعي لدى طلاب الجامعة. • توجد علاقة ارتباطية سالبة دالة إحصائيا بين القلق الاجتماعي، والمهارات الاجتماعية لدى طلاب الجامعة. • توجد فروق دالة إحصائيا في القلق الاجتماعي بين الذكور والإناث لصالح الإناث بينما لا توجد فروق في المهارات الاجتماعية. • توجد فروق دالة إحصائيا في القلق الاجتماعي، بين طلاب الفرقتين الدراسيتين الأولى والرابعة، لصالح طلاب الفرقة الأولى، بينما في المهارات الاجتماعية، لصالح طلاب الفرقة الرابعة. • توجد فروق دالة إحصائيا في القلق الاجتماعي بين الطلاب المقيمين مع أسرهم، والمقيمين في المدن الجامعية لصالح الطلاب المقيمين في المدن الجامعية بينما في المهارات الاجتماعية لصالح الطلاب المقيمين مع أسرهم. توجد بعض العوامل الكامنة المسئولة عن ارتفاع القلق الاجتماعي والمهارات الاجتماعية لدى طلاب الجامعة المقيمين وغير المقيمين بالمدن الجامعية
The present study aimed at investigating social anxiety of University students who were resident with their families and those who were resident at the University guesthouse and its . relationship to their social skills. The sample of the study consisted of (160 Male , Female) Participants from those who were residents at, Alexandria University guesthouse and were selected randomly from the colleges of (Commerce - Social Service, Law , Arts, Engineering. , Science,, Agrictare Medical, Pharmacology. Another random sample were selected from the same colleges and were resident with their families. The second sample consisted of (550) students (270 Males and 380 Females). The clinical sample consisted of two cases (1 Male , 1 Female). The tools of the study included : Social anxiety scale for adolescents and adults designed by the present researcher. Social skill? scale prepared by Mohamed. Abdul Rahman (1992) Interviews designed by the researcher. Case studies prepared by the Amal Baza (1993) Results of the study showed the following: • The ratio of social anxiety were rignfcant spreded for the study sample there was significant prevalence rate of social anxiety for University students. • There was significant negative relationship between social anxiety and social skills for University students. • There were significant differences in social anxiety between males and females, in Faviour of females, while there are no significant differences between males and females in social skills. • There were significant differences between first and fourth grade students in social anxiety in faviour of firsy grade students, while in faviour of fourth grade students in social skills. • There were significant differences between students who resident with their families and those resident in University residence in social anxiety in faviour of students that resident in University guesthouse while in faviour of students who resident with their families in social skills. • Its has been found that there were some hidden factors responsible for increasing social anxiety and social skills for University students.
Keywords: المهارات الاجتماعية -- المدن الجامعية -- المؤسسات الأكاديمية -- الاضطرابات النفسية